Paternal contribution to birth weight. Issue 12 (1st December 2001) - Magnus, P; Gjessing, H K; Skrondal, A; Skjærven, R
Abstract : STUDY OBJECTIVE: Understanding causes of variation in birth weight has been limited by lack of sufficient sets of data that include paternal birth weight. The objective was to estimate risks of low birth weight dependent on parental birth weights and to estimate father-mother-offspring correlations for birth weight to explain the variability in birth weight in terms of effects of genes and environmental factors. DESIGN: A family design, using trios of father-mother-firstborn child. SETTING: The complete birth population in Norway 1967–98. PARTICIPANTS: 67 795 families. MAIN RESULTS: The birth weight correlations were 0.226 for mother-child and 0.126 for father-child. The spousal correlation was low, 0.020. The relative risk of low birth weight in the first born child was 8.2 if both parents were low birth weight themselves, with both parents being above 4 kg as the reference. The estimate of heritability is about 0.25 for birth weight, under the assumption that cultural transmission on the paternal side has no effect on offspring prenatal growth. CONCLUSIONS: Paternal birth weight is a significant and independent predictor of low birth weight in offspring. The estimate of the heritability of birth weight in this study is lower than previously estimated from data within one generation in the Norwegian population.